2016
DOI: 10.1111/jsr.12436
|View full text |Cite
|
Sign up to set email alerts
|

Sleep deprivation increases formation of false memory

Abstract: SummaryRetrieving false information can have serious consequences. Sleep is important for memory, but voluntary sleep curtailment is becoming more rampant. Here, the misinformation paradigm was used to investigate false memory formation after 1 night of total sleep deprivation in healthy young adults (N = 58, mean age ± SD = 22.10 ± 1.60 years; 29 males), and 7 nights of partial sleep deprivation (5 h sleep opportunity) in these young adults and healthy adolescents (N = 54, mean age ± SD = 16.67 ± 1.03 years; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(43 citation statements)
references
References 38 publications
2
30
0
3
Order By: Relevance
“…These findings add to prior investigations performed by our laboratory exploring the cognitive consequences of sleep restriction. These have identified deficits associated with mood, sustained attention, working memory, executive function, speed of processing (Lo et al, 2015(Lo et al, , 2016a, vocabulary learning (Huang et al, 2016) and an increased tendency to form false memories (Lo et al, 2016c). Conversely, memory consolidation seems unaffected (Lo et al, 2016b).…”
Section: Discussionmentioning
confidence: 99%
“…These findings add to prior investigations performed by our laboratory exploring the cognitive consequences of sleep restriction. These have identified deficits associated with mood, sustained attention, working memory, executive function, speed of processing (Lo et al, 2015(Lo et al, , 2016a, vocabulary learning (Huang et al, 2016) and an increased tendency to form false memories (Lo et al, 2016c). Conversely, memory consolidation seems unaffected (Lo et al, 2016b).…”
Section: Discussionmentioning
confidence: 99%
“…Our results con rm this idea. Sleep deprivation affects memory retention, increases erroneous memory formation [57], and is associated with a lack of judgment and attention [58]. Therefore, sleep deprivation from ST just before bedtime could affect attitudes toward learning, learning comprehension, and ultimately, overall academic achievement.…”
Section: Relationship Between St and Each Itemmentioning
confidence: 99%
“…However, it has been questioned whether DRM false memories occur by the same processes as real-world false memories (Frenda, Patihis, Loftus, Lewis, & Fenn, 2014;Ost et al, 2013). Using a richer, more real-world like misinformation task, Frenda et al (2014) and Lo, Chong, Ganesan, Leong, and Chee (2016) found an increase of false memory after sleep deprivation, but not after sleep. The present study aimed to examine the effect of sleep on false memory in a novel manner that more closely resembles real life, using the story-based non-forensic version of the Gudjonsson Suggestibility Scale (GSS) 2 (Gudjonsson, 1987).…”
Section: Introductionmentioning
confidence: 99%